Assessment of Antioxidant, Immunomodulatory Activity of Oxidised Epigallocatechin-3-Gallate (Green Tea Polyphenol) and Its Action on the Main Protease of SARS-CoV-2-An In Vitro and In Silico Approach - Ramakrishna Ungarala; Manne Munikumar; Sukesh Narayan Sinha; Dileshwar Kumar; R. Shyam Sunder; Suresh Challa (MDPI AG, 2022)
Owing to the instability of Epigallocatechin Gallate (EGCG), it may undergo auto-oxidation and form oxidised products or dimers. In the present study, we aimed to evaluate the therapeutic effects, including antioxidation and immunomodulatory action, of the Oxidised Epigallocatechin Gallate (O-EGCG) as compared to native EGCG and the action of these compounds on main protease (Mpro) docking against SARS-CoV-2. HCT-116 (Human Colon Cancer) cell lines were used to estimate the total antioxidant capacity and lipid peroxidation levels and pro-inflammatory markers (human IL-6, IL-1β, TNF-α). Further, molecular docking analysis was performed by AutoDock and visualised in Discovery studio. Improved antioxidant capacity of O-EGCG was observed, and there was a significant decrease in the inflammatory markers (IL-1β, IL-6, and TNF-α) when O-EGCG was applied as compared to EGCG. The O-EGCG was shown to be strongly associated with the highest docking score and active site residues of IL-1, IL-6, and TNF- α, as well as the Mpro of SARS-CoV-2, according to in silico approach. The in vitro and in silico analyses indicate an improved therapeutic action of the oxidised form of EGCG. The effective inhibitory action of O-EGCG against SARS-CoV-2 suggests further exploration of the compound against COVID-19 and its efficacy. However, in vivo studies and understanding of the mechanism of action of O-EGCG may yield a better opinion on the use of O-EGCG and future human clinical trials.